An updated assessment of trends and variability in total and extreme rainfall in the western Pacific. (27th November 2013) - McGree, S.; Whan, K.; Jones, D.; Alexander, L. V.; Imielska, A.; Diamond, H.; Ene, E.; Finaulahi, S.; Inape, K.; Jacklick, L.; Kumar, R.; Laurent, V.; et al.
ABSTRACT Rainfall records for 23 countries and territories in the western Pacific have been collated for the purpose of examining trends in total and extreme rainfall since 1951. For some countries this is the first time that their data have been included in this type of analysis and for others the number of stations examined is more than twice that available in the current literature. Station trends in annual total and extreme rainfall for 1961–2011 are spatially heterogeneous and largely not statistically significant. This differs with the results of earlier studies that show spatially coherent trends that tended to reverse in the vicinity of the South Pacific Convergence Zone (SPCZ). We infer that the difference is due to the Interdecadal Pacific Oscillation switching to a negative phase from about 1999, largely reversing earlier rainfall changes. Trend analyses for 1981–2011 show wetter conditions in the West Pacific Monsoon (WPM) region and southwest of the mean SPCZ position. In the tropical North Pacific it has become wetter west of 160°E with the Intertropical Convergence Zone/WPM expanding northwards west of 140°E. Northeast of the SPCZ and in the central tropical Pacific east of about 160°E it has become drier. Our findings for the South Pacific subtropics are consistent with broader trends seen in parts of southern and eastern Australia towards reduced rainfall. The relationship between total and extreme rainfall and Pacific basin sea surface temperatures (SSTs) has been investigated with a focus on the influence of the El Niño‐Southern Oscillation (ENSO). We substantiate a strong relationship between ENSO and total rainfall and establish similar relationships for the threshold extreme indices. The percentile‐based and absolute extreme indices are influenced by ENSO to a lesser extent and in some cases the influence is marginal. Undoubtedly, larger‐scale SST variability is not the only influence on these indices.